Effectiveness of CSR Programs in The Development of Productive Economic Businesses in Semarang - Soesilowati, Etty; Tri Martuti, Nana Kariada; Nugraha, Satya Budi; Nur Sidiq, Wahid Akhsin Budi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
The purpose of this research is to examine the effectiveness of CSR program distribution in developing productive economy in Semarang City. The study uses a mixed method approach that targets companies that distribute CSR and SMES beneficiary. The SMES sample was taken using the Purposive cluster random sampling technique in each kelurahan, including Culinary business, Agriculture business, Service business, and crafts. Research focuses include: type of company; type of activity ; and the effectiveness of CSR programs with indicators of targeting accuracy, objectives, and benefits. The results showed that 10 companies outside the BUMD that had channeled their CSR funds received a good category with an average value of 79.13 on the Community Development Index. With the highest score in the aspect of suitability of the needs of the community of 83.38 with a good category and the lowest score on the aspect of community involvement was 73.25 with a less good category. Research recommends: first, a pentahelix approach is needed in realizing CSR programs, both between academics as innovators, companies as donors, beneficiary communities and the government as regulators through program integration so that activities are useful; secondly, Bappeda should make a published map of public needs so that academic research and CSR programs are right on target and right on benefits; third, business actors are required to assist business licensing and product marketing through student engagement in KKN programs and promotions by the government both at national and international levels